Limites a eficiência técnica no modo de criação de porcos tradicional do Faxinal - Kolachnek, Luan Matheus Pedrozo (2020)
The objective of this study had been to carry out an investigation on the relationship between the limits of technical efficiency and organization on the way of raising freerange pigs in traditional faxinal communities. Taking into account that the dominant management mode in organizations are aligned with a perspective that prioritizes progressive capital accumulation, targeting the market and technical efficiency in a way that has been directly related to serious environmental and social consequences. In this sense, there is a growing demand for answers to these problems, with special interest in approaches that explore alternative ways of working and organizing that can offer contributions to the field of Organizational Studies. In this way, this work investigated the faxinals, traditional peasant communities typical of southern Brazil that date back to the colonial period. Its production systems are based mainly on the creation of animals in space for community use, with emphasis on pigs. In addition, it presents a combination of subsistence agriculture through private gardens near the residences with one directed to the market through crops. In this study, two traditional faxinal communities were investigated: Papanduva de Baixo, located in the municipality of Prudentópolis/PR and Faxinal do Emboque, in the municipality of São Mateus do Sul-PR. In order to be a case study with a qualitative approach and a descriptive-exploratory nature, semi-structured, unstructured interviews and participant observation were used in order to support content analysis procedures. As a result, it was possible to recognize the existence of limits to technical efficiency in the mode of breeding free-range pigs. They presented operational characteristics, such as the lack of control over the animal, the absence of automation, ambience and the absence of formalization, and evaluative characteristics, such as affection for the animal, the preservation of natural conditions and the set of habits of the residents. In addition, it was possible to recognize that the limits manifested in the production practices proved to be intertwined with structural aspects of the organization of space as a community. In this sense, cultural elements emerged as limiting technical efficiency in the context of faxinals, being characterized by factors of a substantive nature, such as the sense of community, the prevalence of local knowledge and customs and the geographical appreciation of the territory.